2018
DOI: 10.1007/s10554-018-1340-2
|View full text |Cite
|
Sign up to set email alerts
|

Systolic pulmonary artery pressure assessed during routine exercise Doppler echocardiography: insights of a real-world setting in patients with elevated pulmonary pressures

Abstract: Pulmonary hypertension is a marker of disease severity. Exercise Doppler echocardiography (EDE) has proven to be feasible and reliable to assess pulmonary pressure. Increase in systolic pulmonary artery pressure (sPAP) has diagnostic and prognostic value in controlled studies. However, its value when assessed during routine examination in patients with cardiopulmonary diseases and resting sPAP > 35 mmHg is not clearly defined. Clinical documentation and offline reevaluation of digitally stored EDE examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Jüngste Vergleiche zwischen Stressechokardiografie und RHK unter Belastung bestätigen eine Ungenauigkeit der nicht-invasiven Methode [122]. Zu beachten ist, dass ein pulmonalarterieller Druckanstieg unter Belastung jedoch in Abhängigkeit vom untersuchten Patientenkollektiv mit einer besseren (als Surrogat der RV-Funktion bei PAH und CTEPH) oder schlechteren Prognose (als Ausdruck der Schwere einer Linksherzerkrankung) einhergehen kann [123,124]. Die echokardiografische Beurteilung unter laufender PAH-Therapie kann zukünftig eine Bedeutung bei der Verlaufskontrolle erhalten, wobei hier noch Validierungsstudien notwendig sind [125].…”
Section: Stressechokardiografieunclassified
“…Jüngste Vergleiche zwischen Stressechokardiografie und RHK unter Belastung bestätigen eine Ungenauigkeit der nicht-invasiven Methode [122]. Zu beachten ist, dass ein pulmonalarterieller Druckanstieg unter Belastung jedoch in Abhängigkeit vom untersuchten Patientenkollektiv mit einer besseren (als Surrogat der RV-Funktion bei PAH und CTEPH) oder schlechteren Prognose (als Ausdruck der Schwere einer Linksherzerkrankung) einhergehen kann [123,124]. Die echokardiografische Beurteilung unter laufender PAH-Therapie kann zukünftig eine Bedeutung bei der Verlaufskontrolle erhalten, wobei hier noch Validierungsstudien notwendig sind [125].…”
Section: Stressechokardiografieunclassified
“…Korff et al reported conflicting results; a higher TRPG increase during exercise may be a predictor of MACE in patients with any heart disease. 29 They analyzed 278 patients with PASP at rest > 35 mmHg who underwent exercise echocardiography and evaluated the increase in TRPG during exercise. They included patients mainly with ischemic heart disease (49.1%) and valvular disease (22.4%), and their PASPs were moderately increased (rest PASP, 45 mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…Korff et al reported conflicting results; a higher TRPG increase during exercise may be a predictor of MACE in patients with any heart disease 29 . They analyzed 278 patients with PASP at rest > 35 mmHg who underwent exercise echocardiography and evaluated the increase in TRPG during exercise.…”
Section: Discussionmentioning
confidence: 99%